Missing from UNESCO's Roadmap for the Future: The Research Mission of Universities - Philip, Altbach; de Wit, Hans (International Higher Education, 2022)
The 2022 UNESCO Roadmap for the Future only marginally mentions research—while this is a central mission of universities. It is entirely appropriate for most universities to focus mainly on teaching and applied service to society and the economy. Yet, while research-intensive universities only are a small minority worldwide, they are immensely important to global science and innovation. Their function and role do not deserve to be ignored by UNESCO.